Effect of defective NPC three level inverter on nonlinear command of induction motor - Kheira Mendaz; Yamina Benhadda; Houria Bounoua (Serbian Journal of Electrical Engineering, 2022)
Speed Induction Motor (IM) control is an area of research that has been in evidence for some time now. In this paper, a nonlinear controller is presented for the induction motor drives. The nonlinear controller is designed based on an input-output feedback linearization control technique. The input-output feedback linearization control decouples the flux from the speed control and makes the synthesis of linear controllers possible. This article presented input-output linearization control of the induction motor associated with NPC three level inverter defective, the inverter faults are usually caused by operating faults in the switch elements. Switching defects occur in rectifier diodes, the capacitor and inverter IGBT switches. The inverter switches defected reduce the performance of the motor, in our study. We applied the input-output linearization control to test their robustness and performance for detection of fault influence on the physical parameters of the motor, for this purpose, we applied two faults, we started by creating a fault in two switches K1 and K7 which are in the first and second arm of the inverter. Then we created a fault in the three switches K1, K7 and K10 which are in the three arms of the inverter. The simulation results are done by the use of Matlab/Simulink that show the detection, fault effect on input-output linearization control of the different induction motor responses.